REFRAMING SUSTAINABILITY A PERFORMANCE FRAMEWORK FOR PUBLIC EDUCATION AGENCY IN INDONESIA - Amanda Izumi Azalia; Resi Ariyasa Qadri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
Despite Indonesia’s commitment as a member of the United Nations to promote sustainable development, its implementation remains uneven across various sectors, particularly in education. This study aims to develop a comprehensive framework for measuring sustainability performance within public service agency (PSA) in the educational sector. Employing a mixed-methods approach, data were collected through interviews, observations, and document analysis. The findings indicate that educational PSAs have not yet internalized sustainability principles in an integrated manner. To address this gap, the study proposes a novel sustainability performance measurement framework that has been empirically tested through a case study of a civil service college. Unlike existing frameworks, this model is grounded in the ECON-ESG dimensions—comprising economic, environmental, social, and governance aspects—and is refined through expert insights and relevant regulatory adjustments. This framework offers a practical and contextualized tool for evaluating sustainability performance in Indonesia’s educational public service institutions.